SEROLOGICAL DIAGNOSIS OF BRUCELLA ABORTUS : RBPT VIS-A-VIS STAT - Chopra, S; Kumar, Nitesh; Singh, Swatantra K; Tiwari , D (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Serodiagnosis of Brucella abortus infection was carried out on 20 serum samples of cattle and buffaloes using Rose Bengal precipitation test (RBPT) and Standard tube agglutination test (STAT). The study revealed greater sensitivity of RBPT as compared to STAT .